1998
DOI: 10.1021/ac980643l
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor for Direct Determination of Organophosphate Nerve Agents Using RecombinantEscherichia coliwith Surface-Expressed Organophosphorus Hydrolase. 2. Fiber-Optic Microbial Biosensor

Abstract: A fiber-optic microbial biosensor suitable for direct measurement of organophosphate nerve agents was developed. The unique features of this novel microbial biosensor were the recombinant Escherichia coli cells expressing the enzyme organophosphorus hydrolase on the cell surface and the optical detection of the products of enzyme-catalyzed organophosphate hydrolysis. The use of cells with the metabolic enzyme expressed on the cell surface as a biological sensing element provides advantages of no resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 136 publications
(67 citation statements)
references
References 23 publications
(40 reference statements)
1
65
0
1
Order By: Relevance
“…Figure 2A shows the optical images of the PCCA thin film fabricated using different concentrations of monomer. Different amounts of bis/acrylamide monomer solution (5,7,10,15,20,50, 100, and 150 μL from (a) to (h), respectively) were added to the same volume and concentration of polystyrene colloidal suspension with 50 μL of β-CD polymer solution (0.03 g/mL). All samples were fabricated at the same environmental temperature (25 C).…”
Section: Assembly Of Colloidal Crystal Array and The Formation Of Pccmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2A shows the optical images of the PCCA thin film fabricated using different concentrations of monomer. Different amounts of bis/acrylamide monomer solution (5,7,10,15,20,50, 100, and 150 μL from (a) to (h), respectively) were added to the same volume and concentration of polystyrene colloidal suspension with 50 μL of β-CD polymer solution (0.03 g/mL). All samples were fabricated at the same environmental temperature (25 C).…”
Section: Assembly Of Colloidal Crystal Array and The Formation Of Pccmentioning
confidence: 99%
“…13,14 Optical sensors have been developed as one of the promising methods for detection of OP compounds and CNAs which provide more convenient and simple means in optical signal detection. 15 Asher et al have reported the use of polymerized crystalline colloidal array (PCCA) of polystyrene as a novel sensing material for the detection of glucose, organophosphate pesticides and cancer marker with enzyme-based sensors. 16,17 As the PCCA hydrogel undergoes a volume change, the spacing between particles will change, resulting in the shift of reflectance wavelength following Bragg's law.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15] In these reports, cells were usually trapped behind a membrane 13 or encapsulated within a monolithic agarose 11 or poly (vinyl alcohol) cryogel. 15 Then, the product of the substrate reaction with OPH was detected using absorption spectrometry, 11 potentiometry, 13,15 and amperometry. 14 The entrapment of whole cells within polymer matrices provides a convenient preparation of sensors while avoiding the need for enzyme extraction and purification.…”
Section: Introductionmentioning
confidence: 99%
“…With the discovery of organophosphorus hydrolase (OPH), an enzyme that can hydrolyze a wide range of organophosphate pesticides releasing detectable products [16,17], several enzyme and microbial biosensors based on OPH for rapid, simple, selective monitoring of these neurotoxic pesticides with the potential for in the field analysis have been reported [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%